Neurodevelopmental assessment at one year of age predicts neuropsychological performance at six years in a cohort of West African Children - ALAO, MODJÉRÉ OLA MAROUFOU JULES (My University, 2021)
Rural children from Benin, west Africa were evaluated with the Mullen Scales of Early Learning (MSEL) at one year of age and then at six years with the Kaufman Assessment Battery for Children (KABC-II), the visual computerized Tests of Variables of Attention (TOVA), and the Bruininks- Oseretsky Test (BOT-2) of motor proficiency (N = 568). Although both the MSEL and KABC-II were available to the assessors in French, instructions to the mother/child were in local language of Fon. Mothers were evaluated with the Edinburgh Postpartum Depression Scale (EPDS), Caldwell HOME Scale, educational level and literacy, and a Socio- Economic Scale – also in their local language (Fon). After adjusting for maternal factors, MSEL cognitive composite was correlated with KABCII with moderate effect sizes, but not with TOVA scores. Overall etasquared effect for the multivariate models were moderately to strongly correlated (.07 to .37). Neurodevelopmental assessments in early childhood adapted cross-culturally are predictive of school-age neuropsychological cognitive ability.
Keywords: Child development; neurocognition; Mullen; scales of early learning; Kaufman assessment battery for children; tests of variables of attention; Africa